The degree of cross-linking of polyacrylic acid affects the fibrogenicity in rat lungs - Taisuke Tomonaga; Hiroto Izumi; Chinatsu Nishida; Kazuma Sato; Yuiko Nakamura; Toshiki Morimoto; Yasuyuki Higashi; Ke-Yong Wang; Hidenori Higashi; Takuma Kojima; Kazuo Sakurai; Jun-ichi Takeshita; et al. (Scientific Reports)
Abstract Polyacrylic acid (PAA) with different concentrations of cross-linker was instilled into the trachea of rats to examine the effect of PAA crosslink density on lung disorders. Methods: F344 rats were intratracheally exposed to low and high doses of PAA with cross-linker concentrations of 0.1, 1.0, and 5.0% (CL0.1%, CL1.0%, and CL5.0%, respectively). Rats were sacrificed at 3 days, 1 week, 1 month, 3 months, and 6 months after exposure. PAA with different cross-linker concentrations caused an increase in neutrophil influx, cytokine-induced neutrophils, and chemotactic factor (CINC) in bronchoalveolar lavage fluid (BALF) from 3 days to 1 week after instillation. Lactate dehydrogenase (LDH) activity in BALF and heme oxygenase-1 (HO-1) release in lung tissue were higher in the CL0.1% exposure group during the acute phase. Lung histopathological findings also showed that severe fibrotic changes induced by CL0.1% were greater than those observed in CL1.0% and CL5.0% exposure during the observation period. CL0.1% was associated with more severe lung fibrosis, and a decrease in lung fibrosis was observed with increasing cross-linker concentrations, suggesting that the cross-link density of PAA is a physicochemical feature that affects lung disorders.